Trajectories of depressive symptoms and oral health outcomes in a community sample of older adults. (11th May 2015) - Hybels, Celia F.; Bennett, Joan M.; Landerman, Lawrence R.; Liang, Jersey; Plassman, Brenda L.; Wu, Bei
Abstract : Objective: Adverse outcomes associated with chronic depressive symptoms are of clinical importance. The objective was to identify subgroups of older adults based on their trajectories of depressive symptoms over a 10‐year period and determine if these subgroups predicted oral health outcomes. Methods: The sample was 944 adults aged 65+ who participated in the oral health module of the the Health and Retirement Survey in 2008. Depressive symptoms were measured with a modified version of the Center for Epidemiologic Studies‐Depression (CES‐D) scale. Latent class trajectory analysis was used to identify distinct subgroups of elders based on their CES‐D scores from 1998–2008. Group membership was used to predict self‐rated oral health, overall mouth condition (problems with bleeding gums, gum sensitivity, and food avoidance), and edentulism in 2008. Results: Three distinct subgroups were identified using zero‐inflated Poisson regression models: (i) minimal depressive symptoms over the study period (43%), (ii) low but generally stable level of depressive symptoms (41%), and (iii) moderate symptoms and higher CES‐D scores than the other groups over the 10 years (16%). Controlling for demographic and health variables and edentulism status, having a trajectory of moderate symptoms was associated with poorer mouth condition ( p < 0.0001) and poorer self‐rated oral health ( p = 0.0003) compared with those with minimal symptoms. Having low levels of depressive symptoms was not significantly associated with these two outcomes. Group membership was not significantly associated with the probability of edentulism. Conclusions: Chronic moderate depressive symptoms are associated with poorer oral health in older adults. Copyright © 2015 John Wiley & Sons, Ltd.